The Influence of Learning Motivation and Student Perceptions of Teacher Teaching Methods on Biology Learning Outcomes Students on Class X Special Sports (KKO) SMA Negeri 1 Sewon - Basri , Frida Nora Ayu; Irawati, Hani (JURNAL BIOEDUKATIKA, 2023)
KKO is a special class for talented students in the field of sports. Biology scores of KKO students at SMA Negeri 1 Sewon are usually low due to fatigue and many sports activities outside of school. This study aims to determine: (1) The effect of learning motivation on the biology learning outcomes of students in class X KKO SMA Negeri 1 Sewon. (2) The effect of student perceptions of teacher teaching methods on the learning outcomes of students in class X KKO SMA Negeri 1 Sewon. This study uses a quantitative approach with a population of X class students. Data were collected through documentation and questionnaires, and analyzed by simple regression. The results showed: (1) Learning motivation has a positive influence on biology learning outcomes with rx|y 0.745 and r2 xy|0.555. (2) Students' perceptions of teachers' teaching methods als2o have a positive effect on biology learning outcomes with rx|y 0,908 and r y 0,824.x|